Antibacterial activity, stability, and hemolytic activity of heartwood extract from Caesalpinia sappan for application on nonwoven fabric - Tharathip Hemthanon (Elsevier, 2022)
Background: Antimicrobial substances from medicinal plants have been widely applied in many industries, without the concern of side effects. Nonwoven fabric products such as face masks, paper wipes, and wound dressings contain antibacterial substances for reduction of bacterial accumulation. Therefore, the use of bioactive compounds from medicinal plants improves the properties of fabrics. This study used a crude extract from Caesalpinia sappan to perform phytochemical screening and investigate its antibacterial activity, stability, hemolytic activity, and preliminary application in nonwoven fabric products. Results: The alcoholic crude extracts of C. sappan heartwood consisted of alkaloids, anthraquinones, coumarins, flavonoids, saponins, tannins, terpenoids, and cardiac glycosides. The C. sappan extract (CSE) had the highest inhibitory activity against Staphylococcus aureus with inhibition zone of 13.67 ± 1.56 mm in the agar well diffusion assay. The MIC value of CSE was at 1.95, 1.95, and 0.98 mg/ml, while the MBC value was 62.5, 3.91, and 31.25 mg/ml for S. aureus, Bacillus cereus, and Vibrio parahaemolyticus, respectively. The phenolic content was stable at 28 ± 2°C and at pH 4.0 for 12 h (∼95%) and 10 d (>90%), and it had low hemolytic activity on human erythrocytes at 5.04–18.95%. The major chemical component was flavonoids, and brazilein was 1.88% area sum. For the application to antibacterial fabrics, the highest inhibitory activity against S. aureus was found in 2MIC of CSE-coated fabric with 99% for 3 h. Conclusions: The CSE had high inhibitory toward 3 bacterial strains and stability in a wide range of pH and temperature. The CSE-coated nonwoven fabric had efficient inhibition to S. aureus and a possibility to application in a nonwoven product in the future.How to cite: Hemthanon T, Ungcharoenwiwat P. Antibacterial activity, stability, and hemolytic activity of heartwood extract from Caesalpinia sappan for application on nonwoven fabric. Electron J Biotechnol 2022;55. https://doi.org/10.1016/j.ejbt.2021.10.002